The Cultural Dimensions of Legal Certainty: A Study on the Use of Intercultural Knowledge in European Law-Application - Juan Garcia Blesa (European Papers, 2025)
(Series Information) European Papers - A Journal on Law and Integration, 2025 10(2), 405-434 | Article | (Table of Contents) 1. Introduction. – 2. Making European law-application more culturally sensitive: the ECtHR’s application of the legal certainty principle as a case-study. – 2.1. The uncertainties of legal certainty and the ECtHR’s assessment of foreseeability and normative precision. – 2.2. Adding shades of social legitimacy to the ECtHR’s assessment of foreseeability – 3. The cultural dimensions of legal certainty. – 3.1. The study of culture through cultural dimensions. – 3.2. Uncertainty avoidance and legal certainty. – 3.3. Individualism and legal certainty. – 3.4. UA and IDV in the ECtHR’s case-law on legal certainty. – 4. Main theoretical and practical qualifications about the intercultural approach to law. – 4.1. The importance of adopting a nuanced cultural model: the ‘fuzziness’ of culture and the use of macro-level cultural knowledge. – 4.2. Qualifications about the use of cultural dimensions. – 4.3. The question of the generality of norms and non-discrimination. – 5. Final remarks. | (Abstract) The need to take cultural differences into account when dealing with transnational legal problems or implementing legal concepts and principles across countries is widely acknowledged by international institutions and the academia. In this sense, there are important initiatives to funnel ‘external’ cultural expertise into the legal process (e.g. in court proceedings). Yet, the meaningful integration of cultural knowledge into legal work requires lawyers to play an active and guiding role in this exchange so as to shape its modalities, impact and scope. In particular, this involves the identification of professionally intelligible forms of cultural knowledge and the development of potential avenues for their practical integration into legal routines “from within” the legal profession. For this purpose, this article explores the use of the intercultural communication body of knowledge as a means to enrich European human rights adjudication. Focusing on the European Court of Human Rights doctrine on legal certainty and applying intercultural indexes like Uncertainty Avoidance and Individualism to supplement the Court’s assessment of the necessary levels of legal predictability, this work examines the potential viability of relying on that particular body of knowledge for a systematic, large-scale interdisciplinary exchange. With certain qualifications, the conclusions support the advisability of this type of exchange and point to further steps in this direction.